IMPLEMENTATION OF MATHEMATICAL EQUATION FOR CALCULATING ALUMINA EXTRACTION FROM BAUXITE TAILING DIGESTION - Husaini Husaini (Puslitbang tekMIRA, 2016)
Research on bauxite tailing digestion using pressurized batch reactor at a feed capacity of 86.66 kg had been conducted. Bauxite with -150 mesh of particle size is reacted with 42.15 kg of caustic soda (433.49 g/l) at 140oC for 1.0 to 2.5 hours using steam as heating media. Lime added are varied from 3 to 9 kg. After processing for a certain period of time, slurry product is transfered into a mixer. To evaluate percent extraction of Al2O3 from this process, the height of slurry level in the mixer, densities of the slurry, filtrat, and solid residue are measured and determined. The head sample of bauxite, filtrate and residue are analysed by using wet method to obtain Al2O3 content of each sample taken from the mixer. There are four equations that are used for obtaining the alumina extraction, namely : Vsl=4.176x+15.83 Wsl=(4.176x+15.83)ρsl S=(ρsl - ρl)/ (ρs - ρl) (ρs/ ρsl)*100% E=[10 (4.176x+15.83) [1- (ρsl - ρl)/ (ρs - ρl)]*[cl/FxF]% The calculation results show that by increasing lime added into the slurry, percent yield of alumina extraction tend to decrease from 46.63% for 3 kg of lime to 15.84% by using 9 kg of lime. Whereas by varying reaction time between 1.0-2.5 hours, percent yield of alumina extraction are fluctuation in the range of 42.07-60.54%, and the highest result was obtanined for 1,5 hours of reaction time. By implementing those four equations above for evaluating the data, we do not need to weigh the slurry in the reactor.